Menadione is a metabolite of oral vitamin K - Thijssen, Henk H. W.; Vervoort, Lily M. T.; Schurgers, Leon J.; Shearer, Martin J. (British journal of nutrition, 2006)
Phylloquinone is converted into menaquinone-4 and accumulates in extrahepatic tissues. Neither the route nor the function of the conversion is known. One possible metabolic route might be the release of menadione from phylloquinone by catabolic activity. In the present study we explored the presence of menadione in urine and the effect of vitamin K intake on its excretion. Menadione in urine was analysed by HPLC assay with fluorescence detection. Urine from healthy male volunteers was collected before and after administration of a single dose of K vitamins. Basal menadione excretion in non-supplemented subjects (n 6) was 5·4 (sd 3·2) μg/d. Urinary menadione excretion increased greatly after oral intake of the K vitamins, phylloquinone and menaquinone-4 and -7. This effect was apparent within 1–2h and peaked at about 3h after intake. Amounts of menadione excreted in 24h after vitamin K intake ranged, on a molar basis, from 1 to 5% of the administered dose, indicating that about 5–25% of the ingested K vitamins had been catabolized to menadione. Menadione excretion was not enhanced by phylloquinone administered subcutaneously or by 2′,3′-dihydrophylloquinone administered orally. In archived samples from a depletion/repletion study (Booth et al. (2001)Am J Clin Nutr74, 783–790), urinary menadione excretion mirrored dietary phylloquinone intake. The present study shows that menadione is a catabolic product of K vitamins formed after oral intake. The rapid appearance in urine after oral but not subcutaneous administration suggests that catabolism occurs during intestinal absorption. The observations make it likely that part of the menaquinone-4 in tissues results from uptake and prenylation of circulating menadione